Do Third Molars Play a Role in Second Molars Undergoing Endodontic Treatment? - Bilal Kaya; Mehmet Burak Guneser; Betül Aycan Uysal (Cumhuriyet University, 2021)
Background and aim: This study evaluated the rates of second molars undergoing endodontic treatment due to partially or fully erupted lower and upper third molars. Materials and Methods: Radiographic data from 579 patients were analyzed to calculate the rates of second molars undergoing endodontic treatment due to third molars and other reasons. Descriptive statistics were expressed as numbers and percentages for categorical variables. The chi-square test was used to determine the relationships between categorical variables. Results: The rate of second molars undergoing root canal treatment for reasons unrelated to third molars was statistically higher than that of second molars undergoing treatment because of third molars (p < 0.001). The rate of lower second molars with endodontic treatment was significantly higher than that of upper second molars (p < 0.001). There was no statistically significant difference between partially and fully erupted third molars causing root canal treatment of second molars (p = 0.344). Conclusion: Root canal treatment of second molars can be related to fully or partially erupted third molars. All preventive measures should be taken to avoid the need for root canal treatment.